Bancos comunitários de desenvolvimento: o papel da comunicação na economia solidária - COELHO, Celina Leila Chagas de Oliveira (Universidade Federal do Pará, 2015)
The present study aims to analyze the role of communication in solidarity economy and local development, especially in Community Development Banks (BCDs). The primary form of communication to be discussed as a result of the Social Capital and mobilization, because the use of mass comunication is not enough to reach the entire community in which the bank operates. For this purpose the theoretical framework focused on the solidarity economy and the environment; communication; social capital; and social mobilization. Also, it was realized visits to a two BCDs in Manaus, in the Palmas Bank (Fortaleza) and in the Banco Tupinambá (Moqueiro), where a qualitative study of mothers enrolled in the Bolsa Família, Federal Government Program which funds assistance to families living in poverty or extreme poverty, who participate in the project CECI-Mulheres, whose results showed that although the project has been carry out for a year, the participants do not clearly have the basic concepts of Solidarity Economy and BCDs – as women who belong to it are opinion formers, then their position give clues about how the community sees the bank. As part of conclusion of the work, it was realized an assessment about communication channels of Tupinambá Bank emphasizes that the outside communication is more advanced than the inside communication, therefore were made suggestions for new channels focused on mobilization and growth of social capital in Baía do Sol community.